Specificity of Human Resource Management in Social Economy Entities, with Special Reference to Ngos - Schmidt, Joanna (Studia Oeconomica Posnaniensia, 2015)
The aim of this article is to indicate the specific situation and requirements of social economy entities in the area of human resource management and to present solutions specific to the sector. Social economy organizations have to take into account both economic and social criteria in their activities and therefore face ing a number of challenges not only related to the business, but also related to the particular philosophy of management (including managing people) associated with the idea of social economy. Due to the wide variety of legal forms and solutions used amongst social economy entities, the article focuses in particular on non-governmental organizations. The text analyzes NGOs, the key areas of human resource management in the social economy, their role and the tools used in such organizations.